ISOLATION, PCR DETECTION, PATHOTYPING AND ANTIBIOGRAM PROFILING OF ESCHERICHIA COLI ASSOCIATED WITH ENDOMETRITIS IN BUFFALOES - Abhijeet M. Ingale; R. B. Rai1; M. Saminathan; P. Vadhana; S. S. Hingade; K. Dhama; A. A. P. Milton; R. Singh (Journal of Animal and Plant Sciences, 2016)
The aim of the present study was to isolate Escherichia coli from the uterus of buffaloes and to determine its in-vitro sensitivity to commonly used antibiotics. The reproductive tracts (n=103) from the adult buffaloes were collected from Deonar slaughter house, Mumbai, India. Uterine fluid was subjected to isolation of E. coli on eosin methylene blue (EMB) agar; confirmation of isolates by Gram staining, biochemical test and polymerase chain reaction (PCR) using fimH gene, and pathotyping to detect enteropathogenic E. coli (EPEC), enterohaemorrhagic E. coli (EHEC) and enterotoxigenic E. coli (ETEC). The lipopolysaccharide (LPS) concentration from follicular fluid was estimated using chromogenic Limulus amoebocyte lysate assay, histopathology of ovary and uterine tissue samples was done to grade the lesions, and antibiogram of E. coli isolates was carried out to determine sensitivity pattern. Out of 103 cases, 25 samples (24.27%) showed positive for E. coli and only 2 samples showed positive for atypical EHEC pathotype. The LPS concentration in follicular fluid ranged from 0.5 to 4.69 EU/ml and histopathology showed lesions of sub-acute endometritis. The isolated E. coli strains showed good antibiotic sensitivity to tetracycline (100%), cotrimoxazole (100%), gentamicin (90%) and chloramphenicol (88%). However, the isolates were quite resistant to nitrofurantoin (48%) and amoxicillin (41%). In conclusion, the study reported the higher incidence of E. coli, and fimH gene was significantly associated with reproductive disorder (endometritis) and LPS concentration in buffaloes, and the drugs like tetracycline, cotrimoxazole, gentamicin and chloramphenicol could be considered for preventing and treating clinical endometritis in the field. The present study will provide a platform for development of vaccines or therapeutics for E. coli associated endometritis.
Keywords: Buffalo; Uterus; E. coli; Endometritis; Pathotyping; Lipopolysaccharide; Antibiotic sensitivity